Spór Ukraińsko-Rumuński O Wyspę Wężową Zarys problemu – wraz z wyrokiem Międzynarodowego Trybunału Sprawiedliwości ONZ w Hadze z 3 lutego 2009 roku - Donaj, Ł. (Історичний архів. Наукові студії, 2013)
Нині існує маса суперечок з приводу островів у світі. Переможець такого спору
може створити економічну зону навколо острова. Згідно із Законом Моря, її межа
складає 200 м. від берегової лінії. Є тільки одна умова: острів має бути населений.
Однією з проблем незалежної України були неврегульовані стосунки з Румунією. Острів
Зміїний, невеликий острівець у Чорному морі з площею півтора квадратні кілометри,
став синонімом територіальної суперечки. В настоящее время существует масса споров по поводу островов в мире.
Победитель может создать экономическую зону вокруг острова. Согласно Закону
Моря, ее граница составляет 200 м от береговой линии. Есть только одно условие:
остров должен быть населен. Одной из проблем независимой Украины были
неурегулированные отношениями с Румынией. Остров Змеинный, небольшой островок
в Черном море с площадью полтора квадратных километра, стал синонимом
территориального спора. At present, there are dozens of disputes over islands in the world. The winner can create an
economic zone around the island. According to the Law of the Sea, its boundary is 200 m from
the shoreline. There is only one condition: the island must be inhabited. One of the problems of
independent Ukraine was unregulated relations with Romania. Snake Island, a small island in
the Black Sea with an area of one and a half square kilometres, was a synonym of a territorial
dispute. On 3 February 2009, the International Court of Justice decided that Snake Island was
not part of the maritime boundary line (see Attachments 2-3), thus in the dispute between
Romania and Ukraine over the establishment of a maritime boundary and division of the
continental shelf it could not be recognized as the outermost point of Ukraine’s territory. It
seems that the ICJ’s judgment of Solomon in the case concerning the dispute between
Romania and Ukraine (15 judges unanimously agreed that Snake Island was an island entitled
to the 12-nautical-mile arc of the territorial sea, but at the same time the judges established a
new sea border, granting four-fifths of the disputable territory to Romania and the rest to
Ukraine) can set a good example for other states.